Cervical Cerclage versus Vaginal Progesterone for Management of Short Cervix in Low-Risk Women - Wood, Amber M.; Dotters-Katz, Sarah K.; Hughes, Brenna L. (American Journal of Perinatology, 2019)
Objective To evaluate the risk of preterm birth in low-risk women with cervical length (CL) ≤25 mm on transvaginal ultrasound (TVUS) managed with vaginal progesterone (VagP) therapy versus cerclage.Study Design This is a retrospective cohort of women with no prior history of preterm birth or cervical insufficiency and CL ≤ 25 mm on TVUS, managed with either VagP therapy alone or cerclage (with or without VagP). The primary outcome was rate of preterm delivery < 37 weeks gestational age (GA). Secondary outcomes included delivery at ≤ 32 or ≤ 28 weeks GA, premature preterm rupture of membranes, pregnancy latency, GA at delivery, and composite neonatal outcome.Results Women undergoing cerclage placement (n = 31) were older and had an earlier GA at the time of diagnosis of short cervix compared with women receiving VagP (n = 62). Delivery at < 37 weeks occurred in 21/62 (33.9%) in the VagP group and 14/31 (45.2%) in the cerclage group (adjusted odds ratio: 1.72, 95% confidence interval: 0.52, 5.66). There were no differences in secondary outcomes.Conclusion Cerclage compared with VagP therapy did not decrease risk of preterm birth in women with CL ≤ 25 mm. Further research is needed to determine optimal management in such women given a residual 40% risk of preterm birth despite optimal therapy.
Keywords: cervical cerclage; preterm birth; short cervix; vaginal progesterone